Keberlangsungan Kegiatan Keagamaan di Masjid Al-Irsyad Pasca Berdirinya Masjid Raya Sumatera Barat - Al Hadis (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study examines the sustainability of religious activities at Al-Irsyad Mosque before and after the establishment of the West Sumatra Grand Mosque, as well as the contributing factors from mosque administrators and congregants in maintaining these activities despite the presence of the new mosque. The research employs a qualitative descriptive method with a fieldwork approach. Data collection techniques include direct observation, in-depth interviews with mosque administrators and congregants, and documentation of religious activities. Data were analyzed through reduction, presentation, and conclusion/verification, with source, technique, and time triangulation employed to ensure data validity.The results indicate that religious activities at Al-Irsyad Mosque continue consistently in various forms, such as congregational prayers, Qur'anic studies, and other religious-social programs. In fact, new services have been added, such as funeral management, which originated from the initiative of the mosque administrators rather than being influenced by the presence of the Grand Mosque. However, a technical disturbance was identified—namely, the disruption of prayer concentration due to overlapping use of loudspeakers (microphones) from the West Sumatra Grand Mosque when activities occur simultaneously.The sustainability of religious activities at Al-Irsyad Mosque is supported by three main factors: effective and visionary leadership, a strong sense of ownership among congregants, and innovative programs tailored to community needs. The firm commitment of the mosque administrators and the active participation of the congregants are key to ensuring the continued role of Al-Irsyad Mosque as a center for religious life amidst external challenges.